Assessing impacted third molars: Cellular activity in dental follicles and dentigerous cysts - Dipanshu Aggarwal; Arushi Chandra; Sakshi Gupta; Anshi Jain; Devi Charan Shetty (Wolters Kluwer Medknow Publications, 2023)
Background: Dentigerous cysts are among the most prevalent odontogenic cysts associated with impacted teeth, particularly impacted third molars. Understanding the clinicopathological correlation between impacted teeth and factors contributing to cyst formation is essential. Aim: This study aimed to investigate the clinicopathological correlation between impacted teeth and the factors associated with dentigerous cyst formation. Materials and Methods: The study analyzed a total of 30 cases, which were categorized into two subgroups: 16 cases of dental follicles and 14 cases of dentigerous cysts. Retrospective data were collected from the departmental archive, and demographic data along with clinical parameters were correlated. In addition, the Ki-67 index was assessed through immunohistochemical analysis for both study groups. Results: A clinical correlation between impacted teeth along with Ki-67 index in both dental follicles and dentigerous cysts was observed. Conclusion: Based on the findings, it is hypothesized that prophylactic extraction of impacted third molars should be mandatory, irrespective of their symptomatic or asymptomatic status.